The Influence of Green Marketing, Brand Image, Product Quality on Customer Loyalty Reviewed on Islamic Business Perspective - Samsul Maarif; Muhammad Iqbal; Okta Supriyaningsih (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of Green Marketing, Brand Image, Product Quality on customer loyalty reviewed in the Islamic business perspective of the study on consumers MS Glow in Bandar Lampung. The approach in this study is to use quantitative research methods. The population in this study is all customers in Bandar Lampung MS Glow unknown number (unknown population). The number of samples used in this study was 96. The results of this study show that Brand Image and Product Quality individually have a positive and significant impact on customer loyalty. Although Green Marketing does not have a significant individual influence, the three variables of Green Marketing, Brand Image, and Product Quality simultaneously contribute to customer loyalty, implying a complex interaction in which brand image plays an important role when combined with green initiatives and guaranteed product quality.